Language and visuomotor development in children aged 1-3 years in subdistrict bulak, surabaya - Susanti, Dwi (Folia Medica Indonesiana, 2017)
Monitoring childhood activities especially for toddlers is important to review because this period is a golden period for chilhood development. The aim of this research to review determine the prevalence of irregularities childhood development for toddler that aged 1-3 years in District of Bulak, Surabaya. This research is a descriptive cross-sectional study. The study subjects were 98 children aged 1-3 Years that obtained by cluster random sampling. The examination conducted using a screening tool prospective development of the Capute scale (CAT test - SHELL). The result, total of value development (FSDQ) average of 97.88 ± 12.26, visuomotor development value (CAT) average 92.58 ± 16.10 while value language development (CLAMS) average 102.67 ± 13.63. Based on FSDQ score, 84.2% of child had > 85 (normal). The remaining 2.1% including developmental disorders had <75 and 13.7% had score 75-85 (suspected). So, the prevalence of irregularities childhood development for toddlers that aged 1-3 years in District of Bulak around 15.8%.